2022
DOI: 10.2174/1573406417666201204161243
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Clinical Development of Palbociclib: An Overview

Abstract: : Breast cancer is the second most commonly identified cancer in women in the United States after skin cancer. The past few years have seen a substantial increase in breast cancer awareness campaigns and active research in fields of diagnosis and targeted therapy. These factors have led to a better mechanistic understanding of the disease, detection at earlier stages and more personalized approach to treatment, ultimately causing a crucial increase in the survival rates after detection. However, with the advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The flow was subsequently reduced to 0.25 mL min −1 (t r = 3.14 min), and the temperature was incrementally raised to 220 °C (entries 4−8). The adjustments generated increasingly higher yields at each temperature step, resulting in a 43% crude 1 H NMR yield at 220 °C (see SI for the 1 H NMR yield protocol).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The flow was subsequently reduced to 0.25 mL min −1 (t r = 3.14 min), and the temperature was incrementally raised to 220 °C (entries 4−8). The adjustments generated increasingly higher yields at each temperature step, resulting in a 43% crude 1 H NMR yield at 220 °C (see SI for the 1 H NMR yield protocol).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We detected possible inhibitors for the regulation of CEP55 expression or the targeting of CEP55-related pathways and confirmed these using molecular docking analyses. Three smallmolecule compounds were identified that had a strong affinity for CEP55: cytochalasin B, which is a G-actin superimposed inhibitor that can suppress the growth of many types of cancer (Croop and Holtzer, 1975); palbociclib, which is a CDK4/6 inhibitor licensed by the FDA for the treatment of ER+, HER2-breast cancer (Konar et al, 2022), and given that CDK4/6 are critical cell cycle regulators, off-target effects of palbociclib on CEP55 may contribute to its efficacy in triggering tumor cell cycle arrest; and bisbenzimide, which is involved in numerous pharmacological actions, including anticancer, antiparasitic, antibacterial, antifungal, antiviral, and chemosensor activities (Verma et al, 2020). However, the exact effects of these three small compounds on CEP55 remain to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4‐triazole containing molecules played an important role in biological and pharmacological activities. Based on our interest on organic and medicinal chemistry, [86–115] we summarized 1,2,4‐triazoles fused with various other heterocyclic molecules such as pyrimidine, pyridine, piperidine, indole, 1,2,3‐triazole etc. as anticancer agents.…”
Section: Discussionmentioning
confidence: 99%